Comparison of the Mini-Balance Evaluations Systems Test with the Berg Balance Scale in relationship to walking speed and motor recovery post stroke*. Issue 8 (17th November 2017) - Madhavan, Sangeetha; Bishnoi, Alka
Abstract: Background: The Mini-BESTest is a recently developed balance assessment tool that incorporates challenging dynamic balance tasks. Few studies have compared the psychometric properties of the Mini-BESTest to the commonly used Berg Balance Scale (BBS). However, the utility of these scales in relationship to post stroke walking speeds has not been explored. Objectives: The purpose of this study was to compare the sensitivity and specificity of the Mini-BESTest and BBS to evaluate walking speeds in individuals with stroke. Design: A retrospective exploratory design. Methods: Forty-one individuals with chronic stroke were evaluated with the Mini-BESTest, BBS, and 10-meter self-selected walk test (10MWT). Based on their self-selected gait speeds (below or above 0.8 m/s), participants were classified as slow and fast walkers. Results: Significant linear correlations were observed between the Mini-BESTest vs. BBS ( r  = 0.72, p  ≤ 0.001), Mini-BESTest vs. 10MWT ( r  = 0.58, p  ≤ 0.001), and BBS vs. 10MWT ( r  = 0.30, p  = 0.05). Independent t -tests comparing the balance scores for the slow and fast walkers revealed significant group differences for the Mini-BESTest ( p  = 0.003), but not for the BBS ( p  = 0.09). The Mini-BESTest demonstrated higher sensitivity (93%) and specificity (64%) compared to the BBS (sensitivity 81%, specificity 56%) for discriminating participants into slow and fast walkers. Conclusions: The Mini-BESTest has a greater discriminative ability than the BBS to categorize individuals with stroke into slow and fast walkers.